Plaque Wall Distribution Pattern of the Atherosclerotic Middle Cerebral Artery Associates With the Circle of Willis Completeness - Li, Jia; Zheng, Lu; Yang, Wen-Jie; Sze-To, Cheuk-Yin; Leung, Thomas Wai-Hong; Chen, Xiang-Yan (Frontiers in Neurology, 2021)
Objective: Investigating the relevance of the incomplete circle of Willis (COW) to the plaque wall distribution in the atherosclerotic middle cerebral arteries (MCAs) through utilizing high-resolution magnetic resonance imaging (HR-MRI), and its potential clinical impact. Methods: This hospital-based study enrolled consecutive adult patients with acute ischemic stroke or transient ischemic attack, who received a 3.0T Achieva MR system scanning. The COW completeness was evaluated on MR angiography imaging, including anterior (A) and posterior (P)-COW sections. The MCA plaque wall distribution was assessed on HR-MRI. The occurrence of perforator infarction was detected on diffusion-weighted imaging. Results: Among 87 patients (mean age=62.39 ± 11.64 years old) with atherosclerotic plaques in the MCA M1 segments, the incomplete COW types were more prevalent than the complete COW type (incomplete P-COW, 83.9%; incomplete A-COW, 36.8%; complete COW, 8.1%). The incomplete A-COW had more inferior but fewer ventral plaques of MCA atherosclerosis than the complete A-COW, while the incomplete P-COW had fewer inferior MCA plaques than the complete P-COW. Moreover, symptomatic MCA plaques causing perforator infarctions were more likely to locate on the superior wall. Conclusion: Our findings suggested that the COW completeness could influence the vessel wall distribution of the MCA plaques, among which the superior plaques of symptomatic MCA atherosclerosis was associated with branch occlusive disease.